2011
DOI: 10.1111/j.1600-079x.2011.00899.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin supplementation ameliorates oxidative stress and inflammatory signaling induced by strenuous exercise in adult human males

Abstract: Strenuous exercise induces inflammatory reactions together with high production of free radicals and subsequent muscle damage. This study was designed to investigate for the first time and simultaneously whether over-expression of inflammatory mediators, oxidative stress, and alterations in biochemical parameters induced by acute exercise could be prevented by melatonin. This indoleamine is a potent, endogenously produced free radical scavenger and a broad-spectrum antioxidant; consequently, it might have posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 57 publications
(79 reference statements)
3
95
0
1
Order By: Relevance
“…8-OHdG is a DNA base-modified product generated by reactive oxygen species and is a mutation prone to induce a G-C to T-A transversion during DNA replication and has recently been shown to be a new marker of oxidative damage (Fukushima et al, 2010;Huang et al, 1999;Ogonovszky et al, 2005a). Over the past two decades, there is growing evidence that exhaustive exercise increased the MDA and 8-OHdG level in blood, liver and muscle tissues in rat and mice (Liu et al, 2000;Ochoa et al, 2011;Ogonovszky et al, 2005b;Okudan et al, 2012;Voces et al, 1999;Yu et al, 2006). In this study, the data showed that the MDA and 8-OHdG levels in serum, liver and muscle of mice in the CSPtreated groups were significantly lower compared with that in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…8-OHdG is a DNA base-modified product generated by reactive oxygen species and is a mutation prone to induce a G-C to T-A transversion during DNA replication and has recently been shown to be a new marker of oxidative damage (Fukushima et al, 2010;Huang et al, 1999;Ogonovszky et al, 2005a). Over the past two decades, there is growing evidence that exhaustive exercise increased the MDA and 8-OHdG level in blood, liver and muscle tissues in rat and mice (Liu et al, 2000;Ochoa et al, 2011;Ogonovszky et al, 2005b;Okudan et al, 2012;Voces et al, 1999;Yu et al, 2006). In this study, the data showed that the MDA and 8-OHdG levels in serum, liver and muscle of mice in the CSPtreated groups were significantly lower compared with that in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…By the opposite, melatonin counteracts the exacerbated production of infl ammatory cytokines, mainly TNF-α, IL-1β, or IL-6, in several experimental models of infl ammation such as exercise-induced cardiac injury [ 60 ], diabetes-associated low grade of infl ammation [ 61 ], traumatic brain injury [ 62 ], heatstroke-induced multiple organ dysfunction syndrome [ 63 ], ischemia-reperfusioninduced liver damage [ 64 ], neuroinfl ammation in experimental diabetic neuropathy [ 65 ], cerulean-induced pancreatitis [ 66 ], and lung ischemia-reperfusion injury [ 67 ], among many others (reviewed by Carrillo- Vico et al 2013, in press). Furthermore, melatonin reduces the production of infl ammatory markers in infants subjected to endotracheal intubation [ 68 ], preterm newborns with respiratory distress syndrome [ 69 ], and adults under strenuous exercise [ 70 ], as well as in Duchenne muscular dystrophy [ 71 ]. Despite the diversity of infl ammatory conditions tested, the molecular mechanisms of melatonin studied always share the downregulation of the NF-κB activity.…”
Section: Effects Of Melatonin Administration On the Immune Responsementioning
confidence: 98%
“…Melatonin, vitamins C and E, reduced glutathione and uric acid are non enzymatic scavengers [20,21]. Antioxidant enzymes such as Superoxide Dismutase (SOD), Catalase (CAT), Glutathione Peroxidase (GPx), or Glutathione Reductase (GR) are important in the defense against the damaging effect of ROS and RNS [17,22]. Oxidative stress occurs as a result of an imbalance between the excessive production of ROS and RNS and impaired ability of tissue to detoxify free radical in burns.…”
Section: Introductionmentioning
confidence: 99%